Efekivitas Celebrity Endorse, Content Marketing, dan Electronic Word of Mouth (E-WOM) Terhadap Keputusan Pembelian Produk Somethinc di Shopee - Febrianti, Davina Avrilia; Indayani, Lilik; Pebrianggara, Alshaf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the Effectiveness of Celebrity Endorse, Content Marketing, and Electronic Word Of Mouth (E-WOM) on Purchasing Decisions for Somethinc Products at Shopee. Quantitative research was used in this study. Buyers of Somethinc products at Shopee were determined to be the population for this study with the criteria of men and women over 17 years of age. In this study, it was carried out using a non-probability sampling method with a purposive sampling technique of 100 respondents for the sampling technique. The data collection technique in this study was carried out by distributing questionnaires that utilized interval measurements and for answers measured on a Likert scale. The data analysis technique for this study utilizes PLS (Partial Least Square) - SEM (Structural Equation Modeling) with the support of SmartPLS 3.0 software. The results showed that Celebrity Endorse has a positive and significant effect on the Purchase Decision for Somethinc products at Shopee, Content Marketing has a positive and significant effect on the Purchase Decision for Somethinc products at Shopee, and Electronic Word Of Mouth (E-WOM) has a positive and significant effect on the Purchase Decision for Somethinc products at Shopee.